Validation of molecular markers linked to low glucosinolate QTLs for marker assisted selection in Indian mustard (Brassica juncea L. Czern & Coss) - Pushpa, H.D.; Yadava, Devendra K; Singh, Naveen; Vasudev, Sujata; Saini, Navinder; Muthusamy, Vignesh; Prabhu, Kumble Vinod (The Indian Journal of Genetics and Plant Breeding, 2016)
Six earlier reported markers closely linked to low glucosinolate QTLs of Brassica juncea, spread across ‘A’ genome (A2, A3 and A9) were validated in a recombinant inbred line (RIL) population of a cross between Pusa Mustard-21 (low erucic acid) and EC-597325 (double low) genotypes, to utilize them in marker-assisted selection (MAS). Of them, four markers viz., GER 1 amplified alleles of 650 bp and of 950 bp, GER 5 amplified 310 bp and 350 bp, At5gAJ67 amplified 500 bp and 450 bp and Myb28 amplified alleles of size 900 bp and 920 bp in EC597325 and Pusa Mustard-21, respectively and therefore differentiated low and high glucosinolate parents. These four polymorphic markers were then used to genotype the phenotyped RIL population consisting 608 plants. Marker-trait association was tested for goodness of fit using χχ χχ χ2 test. Of the four markers, GER1 and GER5 showed higher phenotypic variance (R2 value) compared to the others, indicating their significance in determination of glucosinolates and prospects for use in MAS for development of Indian mustard genotypes with low glucosinolates content.